Quilting and Sharing: Promoting Lifelong Learning and Service to Others - Jennifer Fortuna (Scholarworks @ WMU, 2020)
Lynne Hall, an occupational therapist, educator, and quilter based in Kalamazoo, MI, provided the cover art for the Winter 2020 issue of The Open Journal of Occupational Therapy (OJOT). "Four Patch Posy" is a 45" x 55" quilt made from cotton. In her 50th year of occupational therapy practice, Lynne's philosophy is rooted in lifelong learning and service to others. The quilt aesthetic provides Lynne a creative medium to serve in her community. With her person-centered approach, Lynne facilitates human potential in the clients, students, and community members she serves. Success in both occupational therapy practice and quilting require a holistic understanding that the whole is greater than the sum of its parts.